DUPLICATION OF SCIENCE BOOKS BY FOTOCOPY BUSINESS SERVICE PROVIDERS IN LAW NUMBER 28 OF 2014 CONCERNING COPYRIGHT - Putri Mardiyah; Irianto, Kartika Dewi; Nazar, Jasman (DE'RECHTSSTAAT, 2024)
Books circulating in the market are relatively expensive and often become a separate obstacle for students to buy the book. Associated with the activity of duplicating books, it is often found among students during college. Students must choose to duplicate the book in the fotocopy business. The research method that the researcher uses is Normative Juridical, therefore it can be concluded 1) The view of Law Number 28 of 2014 Concerning Copyright Against the Duplication of Science Books by Fotocopy Business Service Providers is not included in the violation because it has been explained in article 44 of the Law Copyright The use, retrieval, duplication, modification of a work or related rights product in whole or in substantial part if the source is stated or listed in full for the purpose of duplicating books is permitted for the benefit of science. However, in Article 46 paragraph (1) copying a book by a fotocopying service provider is not considered a copyright infringement if the copying is done only once. 2) Government Efforts in Providing Legal Protection Against Copying Science Books Buying copyrights on the desired books then gives broad access to both educators and students in the digital version for the benefit of the world of education. Updating Law Number 28 of 2014 concerning Copyright in order to provide guarantees to creators and copyright holders to obtain economic rights protection.